Definition of food quality by NMR-based foodomics. (August 2015) - Trimigno, Alessia; Marincola, Flaminia Cesare; Dellarosa, Nicolò; Picone, Gianfranco; Laghi, Luca
Highlights: Foodomics has been proven a promising approach for food quality investigation. NMR has boosted an omic approach to food quality, due to its high reproducibility. A common trait of key foodomics papers is transparency of each investigation step. Advancements in foodomics are foreseen through interdisciplinary networking activity. Abstract : Quality definition of food includes several complex factors like physical, compositional and microbial features, modifications induced by technological processes or storage, nutritional value and safety. Foodomics is a holistic approach applying omics technologies to observe food along the entire production/consumption chain. In the present review, we present key applications of nuclear magnetic resonance in foodomics described in the 2012–2015 period, in the quest for robust and thorough information required by the scientific community. In doing so, we summarize the issues connected to food traceability and authenticity, composition and physical characteristics, processing and storage and health, that mostly impact food quality.